Pain characteristics and analgesic intake before and following cardiac surgery. (February 2016) - Bjørnnes, Ann Kristin; Rustøen, Tone; Lie, Irene; Watt-Watson, Judy; Leegaard, Marit
Background: Cardiac surgery is a common intervention that involves several pain-sensitive structures, and intense postoperative pain is a predictor of persistent pain. Aims: To describe pain characteristics (i.e. intensity, location, interference, relief) and analgesic intake preoperatively and across postoperative days 1 to 4 after cardiac surgery, and to explore associations between postoperative pain and demographic and clinical characteristics. Methods: Four hundred and sixteen patients (24% women) undergoing elective coronary artery bypass grafting and/or valve surgery were enrolled in a randomized controlled trial. Data were collected using standardized measures including the Brief Pain Inventory-short form. A linear mixed model analysis estimated the impact of sex, age, body mass index, analgesic intake and preoperative pain on postoperative worst pain ratings in the previous 24 hours from postoperative days 1 to 4 prior to discharge Results: Thirty-eight per cent of the cardiac surgery patients reported preoperative pain. Postoperative worst pain remained in the moderate to severe range for the majority of patients across day 1 (85%) to day 4 (57%), mainly around the chest incision area for the majority (70%). Mean oral morphine intake was 17 mg/24 h (day 1: 27mg; day 4: 10mg). Lower age, female sex, preoperative pain and analgesic intake had a statistically significant association with higher postoperative worst pain ratings. Conclusion: Study findings demonstrated a high prevalence of moderate to severe pain after cardiac surgery and insufficient analgesic administration. Results indicated that patients were discharged from hospital with unrelieved pain and a potential risk for further postoperative complications.